Sesamin Protects the Femoral Head From Osteonecrosis by Inhibiting ROS-Induced Osteoblast Apoptosis in Rat Model - Deng, Shuang; Zhou, Jian-Lin; Fang, Hong-Song; Nie, Zhi-Gang; Chen, Sen; Peng, Hao (Frontiers in Physiology, 2018)
Glucocorticoids intake has become the most common pathogenic factor for osteonecrosis of the femoral head (ONFH). Annually, tens of millions of patients suffer from pain related to ONFH. Researchers have proposed several underlying mechanisms of ONFH, including osteocyte apoptosis, cell differentiation disorder, and angiogenesis hindrance. Sesamin, isolated from Sesamum indicum seeds, was reported could affect osteocyte inflammation and differentiation in osteoarthritis and osteoporosis. We investigated the underlying influence of sesamin on ONFH rat model. Fifteen male Sprague-Dawley rats were randomly divided into 3 groups. The ONFH model group only received the methylprednisolone and lipopolysaccharide (LPS) injection to promote the development of ONFH. The sesamin treatment group was injected with sesamin, methylprednisolone and LPS. The control group was untreated. Rats from above groups were sacrificed 4 weeks later. The effect of sesamin on ONFH rats was validated by H&E staining. TUNEL staining showed that femoral head necrosis was attenuated by sesamin. Furthermore, the phosphorylation of Akt was increased and the downstream cellular apoptosis signal pathway was inhibited. Intracellular ROS level was decreased after sesamin treatment. In conclusion, our findings suggest that sesamin protects the femoral head from osteonecrosis by inhibiting ROS-induced osteoblast apoptosis.